Burkean identification: Rhetorical inquiry and literacy practices in social media - MacDonald, Lauren E; Walsh, Stephanie L (Journal of Interdisciplinary Studies in Education, 2014)
Through Facebook and Twitter, users now have communities always already available. The dynamic nature of these sites, constantly updating, changing, and shifting, allows for a rich exploration of the nature of self and community. This paper examines such interactions within the “Parlour rooms” of social networks, using Kenneth Burke’s theories on identity as a framework. These platforms offer opportunities for writing teachers to explore rhetorical concepts, develop students’ critical literacy skills, and foster collaborative learning. Considered in the context of computer-mediated communications, Burke’s theories expand traditional notions of the rhetorical concept kairos and, as Cynthia Sheard (1993) notes, enrich our notions of what it means to be spatially, temporally, and rhetorically situated as writers and readers in these digital mediums.